SOME FEATURES OF CHANGING TELOMERE LENGTH IN LYMPHOCYTES FROM THE PATIENTS WITH BRONCHIAL ASTHMA - V. I. Borisov; S. A. Demakov; V. M. Nepomnyashchikh; M. I. Leonova; D. V. Demina; N. A. Barovskaya; V. S. Kozhevnikov (Медицинская иммунология, 2014)
Abstract. A significant telomere shortening was shown in both total peripheral lymphocyte populations and CD4+ T-cells from patients with bronchial asthma, as compared to normal donors. Such shortening takes place in different cell subpopulations depends on different types of bronchial asthma. In patients with intrinsic asthma, a telomere contraction was found both in CD4+ and CD8+T-lymphocytes, but only in CD4+ lymphocytes from patients with extrinsic-type asthma. We didn’t found any changes of telomere length in patients with mixed-type asthma, however, a significant correlation was found between telomere length in both CD4+ and CD8+T- cells, and serum IgE concentrations.The data obtained demonstrate that telomere shortening in lymphocytes may take place not only due to T-cell exhaustion, or homeostatic proliferation induced by lymphopenia, but also due to expansion of antigenreacting cells. The entire data point to sufficient pathogenetic differences for various types of bronchial asthma. A non-uniform contribution of atopic and infectious inflammation may present an important reason for different patterns of the disease development.